LOOSE—LEAF AND ACCOUNTING. - Stoeckel, Herbert J. (The Accounting Review, 1946)
The article presents a brief history of how loose-leaf records of today originated. The year 1946 may be said to mark the fiftieth anniversary of loose-leaf bookkeeping although the first recognized loose-leaf system, the Page-McCleery Order System, had been sold in Chicago, Illinois, at least ten years before in 1896. For many years it had been standard bookkeeping practice to enter orders in a book, fill the orders, and then post the ledger from the order book. Edward C. Page and J. B. McCleery conceived a basic idea whereby salesmen's original orders, recorded on uniform multiple sheets, were inserted in a sheet-holder as received, and, without transcription, were used for selecting, shipping, and billing the order. With the introduction of the new type of ledger, manufacturers who sold their services and loose-leaf systems direct to businessmen sprang up like mushrooms. Competition was keen and often became bitter. Later on, a ruled ledger form and an index were introduced, both on order blank paper which were placed in a transfer binder sold with the company's order system outfit.